The Cultural Identity of Thungsong Railway Platform, Nakhon Si Thammarat Province - Nuang-uthai, Treewanan; Rattanapaijit, Narumon; Keawrod, Ratree (Asian Journal of Arts and Culture, 2025)
The present study aimed to survey and analyze the cultural identity of the railway platform in Thungsong District, Nakhon Si Thammarat Province, which in the past was a very important transportation hub in the area. In-dept interviews were employed to collect data. The findings showed that the platform in Thungsong Junction Railway Station possessed a cultural identity that reflected the way of life and the beliefs of the local community. This identity was outstanding due to a blend of traditional culture and changes from urban and social development. The platform’s role, which connected people in the southern region with other parts of the country was a key factor in creating the unique identity of the Thungsong platform. The way of life of people living around Thungsong Junction Railway Station is mainly about commerce. The cultural identity of Thungsong Railway Junction Platform was its role as a hub city with heavy traveler traffic. Consequently, local people’s way of life was deeply connected with Thungsong Railway Junction. What local people most wished to preserve were Thungsong Junction Railway Station, railway staff houses, the old steam locomotive, local traditions and culture and the people’s lifestyle, respectively. There were additional suggestions from people living around Thungsong Junction Railway Station, proposing the construction of a souvenir shopping center in front of the station, the landscaping improvements at the station and surrounding areas including the railway staff houses. Cleanliness, particularly in public spaces and on roads had to be monitored.